PERAN ANTROPOLOGI PENDIDIKAN DALAM PELESTARIAN BUDAYA ACEH MELALUI PEMBELAJARAN SEKOLAH DASAR - Nurahmi, Fatia; Rahmad Syah Putra; Bansu Irianto Ansari; Udrikal Muna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The preservation of Acehnese culture is a crucial part of efforts to maintain the sustainability of local identity within the framework of the Unitary State of the Republic of Indonesia. Amidst the increasingly strong currents of globalization and modernization, basic education plays a strategic role as a vehicle for transmitting cultural values, norms, and practices to the younger generation. This article aims to analyze the role of educational anthropology in preserving Acehnese culture through learning in elementary schools. The educational anthropology approach provides a conceptual foundation for understanding the relationship between culture, the learning process, and the formation of student character. This research uses a literature review method by reviewing various scientific sources, including journal articles, books, and research findings related to educational anthropology, culture-based basic education, and the preservation of local culture, particularly in Aceh. The study results indicate that integrating Acehnese cultural values ​​into elementary school learning can strengthen students' cultural identity, increase the relevance of learning, and encourage the formation of character rooted in local values ​​such as religiosity, togetherness, and social wisdom. Educational anthropology plays a role in providing an analytical framework for contextualizing learning, avoiding cultural homogenization, and ensuring that education serves as a means of sustainable cultural preservation. This article is expected to make theoretical and practical contributions to the development of basic education that is sensitive to Aceh's local culture.